Hermite-Hadamard type inequalities for product of GA-convex functions via Hadamard fractional integrals - İȘCAN, İmdat; KUNT, Mehmet (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In this paper, some Hermite-Hadamard type inequalities for products of two GA-convex functions via Hadamard fractional integrals are established. Our results about GA-convex functions are analogous generalizations for some other results proved by Pachpette for convex functions. Mathematics Subject Classification (2010): 26A51, 26A33, 26D10.